PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT KAPUAS KABUPATEN SANGGAU - Wilip Alegro Marlanton Nitty E.42008016 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
This research is itended to determines analyzing the effect the motivation on the performance of employesin the head office of the district Kapuas. The research was chosen because of the phenomenon and the problemassociated with the performance of employees in Kapasus districk head office. This is of course related to manyfactors, but the writer has alleged while motivating factor that will either increase the maximum performance foremployees in the head office of the Kapuas.This research is a quantitative hypothesis testing. The population in this study were all employees of theoffice of head Kapuas, except head office. Data collection techniques using a questionnaire that had been testedin advance with the validity and reliability. The data analysis technique used is linear regression nalysis. Theconclusion of this research is the motivation to have significant influence on employee performance 24,7% andthe remaining 75,3% is influenced by other factors not examined.Keyword : Motivation, Employee Performance